OIL SARDINE FISHERY IN THE MANGALORE ZONE DURING THE SEASONS 1963—64 AND 1967—68 - Prabhu, M S; Dhulkhed, M H (Indian Journal of Fisheries, 2011)
The oil sardine fishery in the Mangalore zone showed an upward trend from 1963-64 to 1966-67 when the catches increased seven-fold from 52 to 386 tonnes, which was followed by a slight decline to 243 tonnes in 1967-68. Among the gears operated for the oil sardine fishery, the highest catch-per-unit-efFort values were obtained for the cast net, chala bale and rampant. The best catches of oil sardine were obtained during September-December period when temperature and salinity values ranged 25.5 to 28.6’’C and 28.98 to 34.36 %, respectively. The length frequency studies indicate that the oil sardine attains a size of about 100-110 mm during the first year, 150-160 mm during the second year and 175-180 mm during the third year of its appearance. The fishery during the various years was supported by difierent year classes. One and two-year olds dominated in 1963-64, 1966-67 and 1967-68 and one-year olds in 1964-65. In 1965-66, one-year olds formed the mainstay of the fishery, although the two-year olds also contributed from December onwards. O-year class was seen entering the fishery during the months of August and September in 1964-65, 1965-66 and 1966-67, as also in October and again in January and February during 1967-68. Two or more broods have been observed to enter the fishery during certain years. Judged from the rate of growth and the size attained by the smaller size groups composing the O-year class, the interval between the entries of various broods has been observed to vary from one to three months. The estimated average rate of decrease diu’ing the five-year period worked out to 0.72, the instantaneous rate of mortality being 1.27.